Distribution and sources of SVOCs in fine and coarse aerosols in the megacity of Istanbul - TAYANÇ, METE; FLORES RANGEL, ROSA MARIA (My University, 2022)
© 2022 Elsevier B.V.Approximately 15.4 million people are continuously exposed to various air pollutants in the megacity of Istanbul. Anthropogenic activities in Istanbul generate emissions from mobile sources (i.e., vehicles, aircraft, ships, etc.) and stationary sources such as industrial and residential heating emissions. Biogenic emissions and long-range transport such as desert dust from Sahara and pollutants from Balkan countries also contribute to the local air pollution in Istanbul. In this work, fine (Dp 2.5 μm) particles were collected with a high-volume sampler during four seasons of the period Jan 2017 - Jan 2018. A total of 15 PAHs and 28 n-alkanes were identified and quantified with a newly developed thermal desorption – gas chromatography with mass spectrometry method (TD-GC–MS). Source analysis was performed with PAH and n-alkane diagnostic ratios, and source apportionment was performed with principal component analysis. The yearly averages of PAHs and n-alkanes in the fine fraction were 21.6 ng m−3 and 103.8 ng m−3, with daily averages of 7.1–80.8 ng m−3 and 55.3–204.2 ng m−3, respectively. Approximately 90% of the PAHs and n-alkanes were found in the fine PM fraction in this traffic site. The BaP carcinogenic (BaP-TEQ) and mutagenic (BaP-MEQ) equivalents were on average 5.47 ± 0.64 and 4.72 ± 0.8 ng m−3 in the fine fraction, respectively, and were approximately 6–7 times lower in the coarse fraction. This has important implications due to the respirable nature of fine aerosols and their longer lifetimes in the atmosphere. Multivariate analysis coupled with principal component analysis led to an important result that the organic aerosol mainly originates from two local sources: road traffic (50.4%) and shipping emissions (26.6%). The results found in this work indicate the urgent need for the application of mitigation measures to control road traffic and minimize the emissions from ships passing through the İstanbul Bosphorus.
Keywords: Atmosfer Bilimleri ve Meteoroloji Mühendisliği; Çevre Mühendisliği; Mühendislik ve Teknoloji; Atmospheric Sciences and Meteorological Engineering; Environmental Engineering; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Çevre / Ekoloji; Yerbilimleri; ÇEVRE BİLİMLERİ; METEOROLOJİ VE ATMOSFER BİLİMLERİ; Agriculture & Environment Sciences (AGE); Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENVIRONMENT/ECOLOGY; GEOSCIENCES; ENVIRONMENTAL SCIENCES; METEOROLOGY & ATMOSPHERIC SCIENCES; Aquatic Science; Atmospheric Science; Nature and Landscape Conservation; Environmental Science (miscellaneous); Physical Sciences; Life Sciences; Diagnostic ratios; Megacity; N-alkanes; PCA; PAH; Size distribution; POLYCYCLIC AROMATIC-HYDROCARBONS; PARTICLE-BOUND PAHS; SEASONAL-VARIATION; SIZE DISTRIBUTION; N-ALKANES; EMISSIONS; URBAN; PM10; OXIDATION; PM2.5